2005
DOI: 10.2337/diacare.28.9.2100
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Prandial Glucose Control, and Safety of Insulin Glulisine in Children and Adolescents With Type 1 Diabetes

Abstract: OBJECTIVE -The aim of this study was to investigate the pharmacokinetics, postprandial blood glucose excursions, and safety of insulin glulisine as compared with regular human insulin (RHI), both administered immediately before meals in pediatric patients with type 1 diabetes. RESEARCH DESIGN AND METHODS-A total of 10 children (aged 5-11 years) and 10 adolescents (aged 12-17 years) were enrolled in a randomized, single-center, single-dose, double-blind, cross-over study. The blood glucose of fasting patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
9

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 18 publications
3
56
0
9
Order By: Relevance
“…This trial extends the findings of a previous study comparing glulisine with RHI in children and adolescents with type 1 diabetes, 25 which confirmed that the rapid onset of glulisine observed in adults 6,[26][27][28] is also seen in the pediatric population. Pharmacokinetic studies comparing glulisine and lispro in lean-to-obese subjects without diabetes showed comparable glucodynamic efficacy between both insulins.…”
Section: Discussionsupporting
confidence: 88%
“…This trial extends the findings of a previous study comparing glulisine with RHI in children and adolescents with type 1 diabetes, 25 which confirmed that the rapid onset of glulisine observed in adults 6,[26][27][28] is also seen in the pediatric population. Pharmacokinetic studies comparing glulisine and lispro in lean-to-obese subjects without diabetes showed comparable glucodynamic efficacy between both insulins.…”
Section: Discussionsupporting
confidence: 88%
“…Эффективность и безопасность инсулина глулизин у пациен-тов с СД подтверждена результатами многих клинических иссле-дований [21,22,28]. Два больших исследования III фазы у больных СД1 были посвящены изучению эффективности глу-лизина как компонента базально-болюсного режима в комбина-ции с назначением один раз в сутки беспикового аналога длительного действия инсулина гларгин [21,29].…”
Section: что с практических позиций дают указанные минимальные модифиunclassified
“…В недавнем исследовании 18 пациентов с ожи-рением (ИМТ от 30 до 40 кг/м 2 ) без нарушения углеводного об-мена получали подкожные инъекции глулизина, лизпро и ЧИКД по заранее разработанной схеме [24]. Результаты этого исследования выявили ускоренное начало утилизации глюкозы под действием глулизина и лизпро по сравнению с ЧИКД, при этом инсулин глулизин показал даже более раннее начало ути-лизации и более быстрое время достижения 20% общей утили-зации глюкозы, чем лизпро [28] (рис. 4).…”
Section: сахарный диабетunclassified
See 1 more Smart Citation
“…8 The short-acting profile of insulin glulisine is also maintained across different ethnic groups, paediatric patients and subjects with altered renal function. [9][10][11] The potential advantages of insulin glulisine in obese subjects deserve a separate commentary. It is well known that increased SC thickness alters insulin absorption, shifting the time-action profile curves to the right.…”
Section: Insulin Glulisine -A New Formulationmentioning
confidence: 99%